(untitled) (Journal of Science and Technology, 2016)
The diversity, relative importance, canopy height and cover of plant species in the Kwame Nkrumah University of Science and Technology (KNUST) Botanic Garden were evaluated in five 1-ha plots using a stratified random sampling technique in order to build an understanding of its floristic composition and structure in two distinct parts of the garden (cultivated and uncultivated). We recorded 184 species which belonged to 146 genera, 51 families and six growth forms. The most dominant tree species in the garden were Elaeis guineensis Jacq., Hevea brasiliensis (Willd.) Muell.-Arg. and Parkia biglobosa (Jacq.) G. Don. with a combined importance index of 60.09 (20 % relative importance). The differences in importance value indices of species between the cultivated and uncultivated areas of the garden were statistically insignificant (p > 0.05), suggesting the presence of conducive growth environments for plants in both areas. The most dominant families were Fabaceae, Moraceae, Arecaceae and Euphorbiaceae whilst trees were the most predominant growth forms (62.5 %). Average crown height and percentage canopy were 28.8 ± 8.81 m and 66.4 ± 8.26 % respectively. These results show the floristic richness of the KNUST botanic garden and underscore the garden\’s potential as a centre for ex-situ conservation beside its traditional roles in education, research and recreation.